Thrombotic thrombocytopenic purpura with terminal pancytopenia. Issue 781 (November 1990) - Ng, S. C.; Adam, B. A.
Abstract : A 27 year old housewife developed thrombotic thrombocytopenic purpura during the twelfth week of pregnancy. She had partial response to initial plasma infusion and subsequent plasmapheresis. However, her clinical course was complicated by the development of severe pancytopenia the consequence of a hypocellular marrow. She succumbed to septicaemic shock one month after diagnosis. The development of hypocellular marrow in thrombotic thrombocytopenic purpura has not been reported before.